Analisis Faktor-Faktor yang Berpengaruh Terhadap Pelaksanaan Kewajiban Pihak Pelapor Kepada PPATK - Riskafina Kusuma, Aulia; Susilo Jahja, Adi (CV. Multi Kreasi Media, 2023)
The objective of this research is to assess the impact of return on assets (ROA), return on equity (ROE), and the Reporting Party's training score on PPATK e-learning on the Reporting Party's compliance in carrying out reporting obligations. The findings indicated that the classical assumption test was satisfied in this investigation. The derived multiple linear regression formula is Y = 427.246 – 162.485 X1 + 12.188 X2 – 373.092 X3 + e. The R2 coefficient of determination of 0.757 indicates that the independent variables ROA, ROE, and training score on the number of late Transactions Report (TR) affect 75.7%. The remaining 24.3% was impacted by variables not examined in this research. The partial test shows that the ROA and PPATK e-learning training score have a significant effect on the level of compliance of the Reporting Party in submitting TR in a timely manner. However, the ROE variable does not show any influence on the level of compliance of the Reporting Party in delivering TR in a timely manner. The simultaneous test shows that the ROA, ROE, and score of PPATK e-learning training have a significant effect on the compliance of the Reporting Party in the timely delivery of TR.